How do Female Preferences Influence Political Decisions by Female and Male Representatives? - David Stadelmann; Marco Portmann; Reiner Eichenberger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Exploiting a natural voting experiment we identify female preferences for real policy issues in the electorate. We then analyze whether female or male politicians in parliament more closely correspond to female preferences. Holding constant revealed constituent preferences, there is generally no difference between male and female politicians with respect to representation of female preferences. However, when focusing only on social and redistribution issues, we find that female politicians correspond in their decisions more closely to female preferences.
Keywords: J16; D72; H50; 330